EFL High School Students’ Satisfaction in Online Learning and Expectations Towards Blended Learning: An Investigation - Ningsih, Putu Sri Suci; Santosa, Made Hery; Kusuma , I Putu Indra (Universitas Lancang Kuning, 2023)
This study aims to identify students' satisfaction with online learning and their expectations of blended learning in the post-pandemic era in a senior high public school in North Bali, Indonesia. The research employed an explanatory sequential mixed-method design using questionnaires and interviews, to gather data from 179 grade 12 senior high school students. The questionnaire and interview guide were validated with face, content, empirical validity, and reliability. The interview session involved 5 students with high satisfaction scores and 5 students with low satisfaction scores from the result of the questionnaire. The results showed that students had a mode score of 4, indicating students feel satisfied with online learning during COVID-19. Based on the four factors, the result of students’ satisfaction in online learning such as the teacher factor having neutral scores, the interaction factor having satisfied scores, the technology factor having satisfied scores, and the course management factor having satisfied scores. The interview session shows that students expressed their expectations for direct interaction with teachers and classmates and had expectations for factors, such as teaching methods, ease of materials, direct communication with teachers, interaction with classmates, technology use, and variety in learning resources. This research provides insights for teachers to improve student satisfaction with online learning and blended learning practices.